Morphological System of the Simalungun Batak Language: A Study of Generative Transformation - Murni Simarmata; Immanuel Silaban; Ridho Wahyu Cristian Silaban; Andreas Alessandro Hutagalung; Johannes Pandiangan; Jonathan Halomoan Marpaung (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The purpose of this research is to study the morphological structure of the Toba Batak language from the perspective of generative transformation studies. The primary issue in this microlinguistic research is the process of word formation through the mechanisms of affixation, reduplication, and composition. Previous research on word forms in the Simalungun Batak language has been based on structural morphological theory, which only examines linguistic phenomena superficially. Therefore, linguistic phenomena that actually occur in the field are often overlooked because the theories used are unable to fully explain them. This research uses a qualitative descriptive method. This approach was chosen because it aims to describe in depth and structure phenomena related to word structure in the Simalungun Batak language (BBS) from the perspective of Generative Morphology Theory. The results of this study indicate that the morphological system of the Simalungun Batak language describes in depth and structure phenomena related to word structure in the Simalungun Batak language (BBS) from the perspective of Generative Morphology Theory. The first issue in this research is the process of word formation through the mechanisms of affixation, reduplication, and composition, which only examines linguistic phenomena superficially.